Diálogos entre ciências e ficção científica: uma estratégia para discutir ética científica baseada na teoria da objetivação - Nogueira, Mayara Larrys Gomes de Assis (2019)
Science Fiction (SF) often presents science as a living and inspiring activity that seems to fuel interest and curiosity over complex scientific issues. This proposition contrasts with some scenarios described in the specific literature in which discussions about science products and processes in the classrooms seems increasingly uninteresting to students. In this summary, I propose a strategy to come across the classroom disinterest on science topics and to discuss epistemological aspects of sciences by opening a dialogue between Sciences and Literature. More specifically, I have taken SF literature as a language to discuss the notion of ethics in science. These ideas are based philosophically, pedagogically and epistemologically on the Theory of Objectification (TO), a cultural-historical theory of teaching and learning idealized by the mathematical researcher Luis Radford. The thesis aims to investigate the relevance of SF as a strategy to expand, promote and contextualize the discussions about sciences making and its ethical aspects for pre-service science teachers. To achieve this, I used three methodological strategies: an epistolary interlocution with the fictional scientist Doctor Victor Frankenstein; an immersion in theoretical basis such as the discussions about science, the TO and the SF; and, finally, the production of teaching strategies – an exploratory educational workshop taught to pre-service science teachers from the Programa Institucional de Bolsa de Iniciaçào Científica (PIBID/Interdisciplinar) at Universidade Federal do Rio Grande do Norte (UFRN) to map approach of students with the language of SF and a course about Science Fiction and Ethics in Sciences offered to pre-service and professional teachers of the Chemistry, Physics, Biology and Mathematics undergraduate courses at UFRN, the Instituto Federal de Educação Ciência e Tecnologia do Rio Grande do Norte (IFRN) and the University Center Facex (UniFacex). For instance, the epistolary dialogue with Victor Frankenstein to discuss ideas, employ debates and exercises about ethics and scientific responsibility and was a way of taking SF as a language to approach knowledge about sciences' epistemology. Furthermore, the multimodal analysis of the data produced allowed to establish a set of analytical categories, vectors, and paths to map them supported the relevance of strategies that use SF as a language to bring students closer to scientific culture. This scenario is fertile to argue that SF is a relevant language to think about and problematize discussions about sciences' ethical aspects and can contribute to the scientific education of pre-service science teachers.